Comparison of Baby Massage and Baby Gym on the Growth and Development of Infants Aged 6–12 Months at the Dince Safrina Maternity Clinic - Dany Ariyani; Linda Suryani; Siska Mulyani (IKES Payung Negeri Pekanbaru, 2025)
The importance of early stimulation for infants lies in the fact that their growth and development are influenced by various internal and external factors. One effective form of stimulation within the midwife’s scope of practice is Baby Spa, which includes baby massage, baby gym, and baby swimming. Specifically, baby massage is known for its benefits in improving weight gain, sleep quality, and emotional bonding, while baby gym plays a role in optimizing motor development, muscle strength, and coordination. This study aims to compare the effectiveness of baby massage and baby gym on the growth and development of infants aged 6–12 months. The methodology used was a quasi-experimental pretest-posttest design with a control group. A total of 40 infants were equally divided into two groups: 20 infants received baby massage (intervention group) and 20 infants received baby gym (control group). Both interventions were administered 8 times, twice a week, with a duration of 30 minutes per session. Infant development was measured using the SDIDTK (Early Childhood Development Stimulation, Detection, and Intervention) Form before and after the intervention. Data were analyzed using the Mann Whitney test and Paired t-test. The results showed that both baby massage and baby gym had a significant effect on improving infant growth (weight and length), with a P-value of 0.000 (P < 0.05) for both interventions. However, further comparative analysis revealed a significant difference in the effects of the two interventions in improving growth (weight P = 0.00; height P = 0.000) and development (P = 0.00). It was concluded that there is a difference in effectiveness between baby massage and baby gym as stimulation interventions for infants aged 6–12 months. The researchers recommend enhancing education for mothers on the importance of stimulation for infants aged 6–12 months